The use of time study, method study and GPS tracking in improving operational harvest planning in terms of system productivity and costs - Odhiambo, Benedict O. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScFor (Dept. of Forest and Wood Science)--University of Stellenbosch, 2010.